Ответы и объяснения

  • 2407Alexa
  • почетный грамотей
2013-12-07T20:20:34+04:00
1)S(n)=((a1+an)/2)n
2)an=a1+d(n-1)
n=4
n=6
S4=((a1+a4)/2)*4=2*(a1+a4)
S6=((a1+a6)/2)*6=3*(a1+a6)
a4=a1+d(4-1)
a6=a1+d(6-1)
a4=a1+3d
a6=a1+5d
S4/2=a1+a1+3d=2a1+3d=-14
S6/3=a1+a1+5d=2a1+5d=19,34
2a1+3d-2a1-5d=-14-19,34
-2d=-33,34
d=-33,34/-2
d=16,67
2а1+5d=19,34
2a1=19,34-5d=18-5*16,67=19,34-83,35=-64,01
a1=-64,01/2
a1=-32,005
по Ф. 2) найдем а16=a1+15d
a16=-32,005+15*16,67=218,045
по ф. 1) S16=((-32,005+218,045)/2)*16=
=186,04*8=1,488,32
Вроде бы не ошиблась.